Ответы и объяснения

2013-06-05T13:15:34+00:00

1)3с^2-16

2)2a^2-9

3)3y^2+3

4)4c^2+4

5)2b^2+2a^2

6)3x^2+3y^2

7)2a^2-9

8)16-6a^2

9)y^2

10)-b^2

11)-5a^2+21

12)-x^2-8

13)5c

14)-11a

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

Лучший Ответ!
  • Keelat
  • светило науки
2013-06-05T13:32:02+00:00

1) 4c*(c-2) - (c-4)^2 = 4c^2 - 8c - c^2 + 8c - 16 = 3c^2 - 16

2) 3a*(a+2) - (a+3)^2 = 3a^2 + 6a - a^2 - 6a - 9 = 2a^2 - 9

3) 3*(y-1)^2 + 6y = 3y^2 - 6y + 3+ 6y = 3y^2 + 3

4) 8c + 4*(1-c)^2 = 8c + 4 - 8c + 4c^2 = 4c^2 + 4

5) 4ab + 2*(a-b)^  = 4ab + 2a^2 - 4ab+ 2b^2 = 2a^2 + 2b^2

6) 3*(x+y)^2 - 6xy = 3x^2 + 6xy + 3y^2 - 6xy = 3x^2 + 3y^2

7) 3a*(a-2) - (a-3)^2 = 3a^2 - 6a - a^2 + 6a - 9 = 2a^2 - 9

8) (a-4)^2 -2a*(3a-4) = a^2 - 8a + 16 - 6a^2 + 8a = -5a^2 + 16

9) (x-y)^2 -x*(x-2y) = x^2 - 2xy + y^2 - x^2 + 2xy = y^2

10) a*(a+2b) - (a+b)^2 = a^2 + 2ab - a^2 - 2ab - b^2 = -b^2

11) (a-3)*(a-7) -2a*(3a-5) = a^2 - 7a - 3a + 21 - 6a^2 + 10a = -5a^2 + 21

12) (x-2)*(x+4) -2x*(1+x) = x^2 + 4x - 2x - 8 - 2x - 2x^2 = -x^2 - 8

13) 2c*(3c+4) - 3c*(2c+1) = 6c^2 + 8c - 6c^2 - 3c = 5c

14) 3a*(2a-1) -2a*(4+3a) = 6a^2 - 3a - 8a - 6a^2 = -11a